(untitled) (Bangladesh Medical Journal Khulna, 2016)
Stroke is the leading cause of adult disability and is the third commonest cause of death worldwide. It is a major cause of morbidity and mortality with disability and social dependence throughout the world. An observational, descriptive, cross-sectional study was conducted among purposively selected one hundred and seventy patients with stroke admitted at Kushtia Medical College Hospital, Kushtia from July 2014 to June 2015 to evaluate the different modifiable risk factors and their frequency among stroke patients. Stroke patients with more than 24 hours duration presenting within seven days of onset irrespective of age, sex and demographic profile were included in the study. After obtaining informed consent, patients who fulfilled the inclusion criteria were thoroughly evaluated for the presence of risk factors. Data were collected by investigators themselves. Out of 170 confirmed cases of stroke, 89 (52.35%) were male, while 81 (47.65%) were female. Mean age of the patients was 63.74 years with a standard deviation of 16.5 years. The highest incidence 43 (24.70%) of stroke was in the age group of 60 to 69 years. As many as 122 (71.76%) had ischaemic stroke, while 48 (28.24%) had haemorrhagic stroke. At least 119 (70.00%) cases were hypertensive. 41 (24.11%) cases had diabetes mellitus, 31 (18.23%) had hyperlipidaemia, 52 (30.6%) were smokers and 25 (14.70%) had past history of stroke. Among 81 female patients, 66 (81.48%) were in post-menopausal, whereas 15 (18.52%) were in the reproductive age group. Of them 5 (33.33%) had history of taking oral hormonal contraceptive. Hypertension, smoking, diabetes mellitus and hyperlipidaemia are the identified modifiable risk factors associated with stroke. Bang Med J (Khulna) 2015; 48 : 24-27